STUDI KELAYAKAN PERANCANGAN GALANGAN KAPAL DI KABUPATEN WAKATOBI - Edi Fedriansyah; Ali Azhar (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
Until now, there is no shipyard company for ship maintenance and repair in Wakatobi. This study aims to determine the location of the shipyard and a technical feasibility study of the shipyard. Based on the results of the field surfey, there are two (2) locations, namely Matahora Village, Wangi-Wangi Selatan District, Wakatobi Regency (location 1) and Dete Village, East Tomia District, Wakatobi Regency (location 2) which can be used as service providers. This study uses the Analytical Hierarchy Process (AHP) method to compare the two locations by considering the criteria of geography, infrastructure, materials and logistics, modes and transactions and markets. so that the results obtained location 1 is superior with an assessment weight obtained of 0.75 (75%). Referring to the government regulations regarding industrial estates, the location determined is said to be feasible, where this location has land right on the beach with a sea depth ranging from 2-5 meters and the planned location area is 3 hectares.